Legal Protection of Film Copyright Holders Against the Distribution of Free Film in Telegram Media - Isrok, Mohammad; Hilmy Rizqullah Ramadhan, Muhammad; Anggraeny, Isdian; Cindy Monique, Cindy Monique (KnE Social Sciences, 2022)
Copyright is an exclusive right owned by someone who creates a product that can be realized in a tangible form without compromising the laws and regulations. The function of copyright is protection of the work inherent in the maker, but it is the best compared to the reality in the field. In Internet media, in this case, telegrams are widespread and accessible regarding film series, the legal phenomenon violates copyright in the film works made by someone even though the legal protection arrangements for copyright have been regulated in Law Number 28 of 2014 concerning Copyright and are also contained in Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions. Of course, law enforcement and legal efforts need to be carried out through various solutions which will be discussed later in this paper where the method used in this paper uses normative juridical research with literature and assesses several relevant laws and regulations using qualitative descriptive analysis techniques. The study results indicate that the regulation regarding Law Number 28 of 2014 and its joint ministerial regulation has not been effective and does not work for the legislation to protect copyrights for works owned by someone. Keywords: copyright, films, legal protection, telegram